LO QUE EL USO DE LAS CONSTRUCCIONES CON O SIN MÍ Y CON O SIN TI NOS MUESTRA SOBRE LA ESTRUCTURA DE LA LENGUA. - Echeverría Arriagada, Carlos I. (Estudios Románicos, 2016)
This paper centers around the disjunctive constructions con o sin mí and con o sin ti as alternatives to conmigo o sin mí and contigo o sin ti in Spanish, for the implications of their use for the subject of the compatibility between the preposition con and the personal pronouns mí and ti and, on a more general level, of the language value of these pronouns. Attention is drawn to the confirmation of a non-negligible number of cases of the former constructions, which may be considered "uncanonical", due to the fact that, in them, con and the pronoun contract the same syntagmatic relation as in the now disused and frowned-upon constructions con mí and con ti. The apparent paradox is explained in terms of the Coserian distinction between system and norm, thus serving as an example to clarify the meaning and relevance of said distinction. Finally, the paper closes with some reflections on the way languages are historically constituted.